Natural 15N abundance of ammonium and nitrate in soil profiles: New insights into forest ecosystem nitrogen saturation. Issue 3 (16th March 2022) - Gurmesa, Geshere Abdisa; Hobbie, Erik A.; Zhang, Shasha; Wang, Ang; Zhu, Feifei; Zhu, Weixing; Koba, Keisuke; Yoh, Muneoki; Wang, Chuankuan; Zhang, Qiuliang; Fang, Yunting
Abstract: Assessment of nitrogen (N) saturation of forests is critical to the evaluation of the manner in which ecosystems will respond to current and future global changes such as N deposition. However, quantifying N saturation remains a challenge. We developed a conceptual model of N saturation stages in forest ecosystems based on (1) a hypothetical relative rate of ammonification, nitrification, and denitrification, (2) concentrations of ammonium and nitrate in the soil, and (3) 15 N enrichment pattern of bulk soil N, ammonium, and nitrate in the soil profile. We tested the hypotheses using data from forests located at five sites across eastern Asia. The fraction of nitrate in total inorganic N indicated that the sites represent an N saturation gradient with one boreal forest at stage 1 (least saturated), three temperate forests at stage 2, and one tropical forest at stage 3 (most saturated). The δ 15 N of bulk soil N increased from topsoil to subsoil more sharply at N‐limited sites than at the N‐rich sites along the N deposition gradient. We also found distinct 15 N enrichment patterns of bulk soil N, ammonium, and nitrate in the soil profile across the study sites. At stage 1, nitrate was more 15 N‐depleted than ammonium only in the organic soil horizon, indicating limited nitrification, while the 15 N depletion of nitrate to ammonium was observed in the deeper mineral soil at stages 2 and 3. Furthermore, ammonium was more 15 N‐depleted than bulk soil N at stages 1 and 2 but more 15 N‐enriched than bulk soil N at stage 3. Our study suggests that soil profile patterns of δ 15 N of bulk soil N, ammonium, and nitrate provide information about the relative rates of mineralization, nitrification, and denitrification and thus can be an additional measure of N saturation of forest ecosystems across broad environmental gradients.